INCREASING STUDENT UNDERSTANDING ON PPKN STUDY THROUGH THE DEBATE MODEL TO THE LEGISLATION MATERIALS - Rosmiati, Yatti (Universitas Pendidikan Indonesia, 2024)
This Classroom Action Research aims to improve the learning outcomes and activities of class VIII A students in PPKn lessons on legislation material through the application of debate learning models. The results of the pre-research obtained an average score of 55.87, completed 2 people or 5%. After reflection, the average score in cycle II increased to 86.34 in the